Fertilizer Rate-Associated Increase in Foliar Jasmonate Burst Observed in Wounded Arabidopsis thaliana Leaves is Attenuated at eCO2 - Martinez Henao, Julian; Demers, Louis Erik; Grosser, Katharina; Schedl, Andreas; van Dam, Nicole M.; Bede, Jacqueline C. (Frontiers in Plant Science, 2020)
The predicted future increase in tropospheric carbon dioxide (CO2) levels will have major effects on C3 plants and their interactions with other organisms in the biosphere. In response to attack by chewing arthropod herbivores or nectrotrophic pathogens, many plants mount a rapid and intense increase in jasmonate-related phytohormones that results in a robust defense response; however, previous studies have shown that C3 plants grown at elevated CO2 may have lower induced jasmonate levels, particularly in well nitrate-fertilized plants. Given the relationship between atmospheric CO2, photorespiration, cellular reductant and redox status, nitrogen assimilation and phytohormones, we compared wound-induced responses of the C3 plant Arabidopsis thaliana. These plants were fertilized at two different rates (1 mM or 10 mM) with nitrate or ammonium and grown at ambient or elevated CO2. In response to artificial wounding, an increase in cellular oxidative status leads to a strong increase in jasmonate phytohormones. At ambient CO2, increased oxidative state of nitrate-fertilized plants lead to a robust 7-iso-jasmonyl-L-isoleucine increase in wounded plants; however, the strong fertilizer rate-associated increase is alleviated in plants grown at elevated CO2. As well, the changes in ascorbate in response to wounding and wound-induced salicylic acid levels in plants may also contribute to the suppression of the jasmonate burst. Understanding the mechanism underlying the attenuation of the jasmonate burst at elevated CO2 has important implications for fertilization strategies under future predicted climatic conditions.